Opening high-speed railway’s influence on high-quality economy in China’s counties - Liao, Xianchun; Yan, Xu; Ji, Hairui (Frontiers in Environmental Science, 2023)
Improving county economy is the key to realize high-quality economy and “dual carbon” target for developing countries like China. Taking opening high-speed railway as an entry point, we explore its impact mechanism in counties in Yangtze River’s upper reaches by applying entropy weight method (EWM) to estimate the high-quality economy and multi-period Propensity Score Matching (PSM)-difference in difference (DID) methods to perform empirical analysis with panel data of 396 counties from 2006 to 2018. Results demonstrate that implementing high-speed railway remarkably promotes high-quality economy at county level, which is stable after a series of verification. We also solve endogeneity with instrumental variable method (IV) and systematic Generalized Method of Moment (GMM). Further heterogeneity analysis reveals that opening high-speed railway positively accelerates high-quality economy of counties above average and mediating effect analysis reveals adjustment of industrial structure is main channel. Accordingly, the findings provide policy implications.